Perlindungan Hukum terhadap Penyandang Disabilitas sebagai Korban Perundungan dalam Perspektif Hukum Positif Indonesia - Mutiara Sari br Tarigan (Jurnal Hukum Lex Generalis, 2026)
Legal protection for persons with disabilities aims to ensure legal certainty, equality, and non-discrimination before the law. However, social stigma related to the physical and sensory conditions of persons with disabilities continues to make them vulnerable to bullying. This study aims to examine the legal framework governing the protection of persons with disabilities as victims of bullying within the national legal system, as well as the criminal sanctions imposed on perpetrators. The research employs a normative legal method using statutory, jurisprudential, and legal literature approaches. The findings indicate that legal protection for persons with disabilities is regulated under Law Number 8 of 2016 concerning Persons with Disabilities. The effectiveness of such protection is influenced by law enforcement, supporting facilities, and public awareness.